1997
DOI: 10.1002/(sici)1096-9837(199705)22:5<473::aid-esp710>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Yield During Late Glacial and Holocene periods in the Lac Chambon Watershed, Massif Central, France

Abstract: A sediment budget for the Late Glacial and Holocene periods was calculated for the Lac Chambon watershed which is located in a formerly glaciated temperate crystalline mountain area. It appears that over 15 500 years: (1) 69 per cent of eroded particles have been displaced by gravity processes and then stored within the watershed, compared to 31 per cent that have been displaced by running water and evacuated outward; (2) the mean mechanical erosion due to gravity processes on the slopes amounted to 16·1± 6 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A study of the Lac Chambon infill and sediment budget during the last 13 ka (Macaire et al, 1997) demonstrated a climate-dependent erosion rate ranging from 50 m 3 / km 2 /yr (= 50 mm/ka) during the Bölling interstadial to 120 m 3 / km 2 /yr (= 120 mm/ka) during the Younger Dryas stadial and returning again to 50 m 3 /km 2 /yr (= 50 mm/ka) during the prehistoric Holocene. A study of the Lac Chambon infill and sediment budget during the last 13 ka (Macaire et al, 1997) demonstrated a climate-dependent erosion rate ranging from 50 m 3 / km 2 /yr (= 50 mm/ka) during the Bölling interstadial to 120 m 3 / km 2 /yr (= 120 mm/ka) during the Younger Dryas stadial and returning again to 50 m 3 /km 2 /yr (= 50 mm/ka) during the prehistoric Holocene.…”
Section: Landscape Erosion Ratesmentioning
confidence: 99%
“…A study of the Lac Chambon infill and sediment budget during the last 13 ka (Macaire et al, 1997) demonstrated a climate-dependent erosion rate ranging from 50 m 3 / km 2 /yr (= 50 mm/ka) during the Bölling interstadial to 120 m 3 / km 2 /yr (= 120 mm/ka) during the Younger Dryas stadial and returning again to 50 m 3 /km 2 /yr (= 50 mm/ka) during the prehistoric Holocene. A study of the Lac Chambon infill and sediment budget during the last 13 ka (Macaire et al, 1997) demonstrated a climate-dependent erosion rate ranging from 50 m 3 / km 2 /yr (= 50 mm/ka) during the Bölling interstadial to 120 m 3 / km 2 /yr (= 120 mm/ka) during the Younger Dryas stadial and returning again to 50 m 3 /km 2 /yr (= 50 mm/ka) during the prehistoric Holocene.…”
Section: Landscape Erosion Ratesmentioning
confidence: 99%